Unlocking the Secret to a Healthy Gut - Saji, Elsa (SciWise, 2025)
A lay summer presenting the results of Ugai et al., 2025 study on long-term yogurt intake and colorectal cancer incidence. Original Paper DOI: https://doi.org/10.1080/19490976.2025.2452237.